2012
DOI: 10.1002/brb3.96
|View full text |Cite
|
Sign up to set email alerts
|

The effects of MAOA genotype, childhood trauma, and sex on trait and state‐dependent aggression

Abstract: Monoamine oxidase A (MAOA) genotypic variation has been associated with variation in aggression, especially in interaction with childhood trauma or other early adverse events. Male carriers of the low-expressing variant (MAOA-L) with childhood trauma or other early adverse events seem to be more aggressive, whereas female carriers with the high-expressing variant (MAOA-H) with childhood trauma or other early adverse events may be more aggressive. We further investigated the effects of MAOA genotype and its int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…The LEIDS-r has a total score, and six subscales assessing cognitive reactivity related to Aggression, Hopelessness/Suicidality, Acceptance/Coping, Control/Perfectionism, Risk Aversion, and Rumination on Sadness. LEIDS-r scores were found to be associated with depression history over and above rumination [36], to be associated with genetic markers of depression [23], [37], [38], and with response to tryptophan depletion, reflecting biological vulnerability to depression [22]. Moreover, treatment and other longitudinal studies support the validity of the LEIDS-r as a measure of depression vulnerability [39], [40], [41], [42].…”
Section: Methodsmentioning
confidence: 75%
“…The LEIDS-r has a total score, and six subscales assessing cognitive reactivity related to Aggression, Hopelessness/Suicidality, Acceptance/Coping, Control/Perfectionism, Risk Aversion, and Rumination on Sadness. LEIDS-r scores were found to be associated with depression history over and above rumination [36], to be associated with genetic markers of depression [23], [37], [38], and with response to tryptophan depletion, reflecting biological vulnerability to depression [22]. Moreover, treatment and other longitudinal studies support the validity of the LEIDS-r as a measure of depression vulnerability [39], [40], [41], [42].…”
Section: Methodsmentioning
confidence: 75%
“…Indeed, most lines of evidence have shown that, in women, high-activity MAOA variants and their interactions with early adversities, predict for externalizing behaviors and aggression (Kinnally et al, 2009; Beach et al, 2010; Åslund et al, 2011; Verhoeven et al, 2012; McGrath et al, 2012; Holz et al, 2014; but see also Ducci et al, 2008 for evidence pointing to homozygous low-activity genotype as a risk factor for antisocial behavior in females). Further studies are warranted to examine how MAOA may impact aggression risk in a sex-dependent fashion.…”
Section: Role Of Maoa Allelic Variants In the Ontogeny Of Aggressionmentioning
confidence: 99%
“…In this manner, males with low MAO-A activity genotype who have been exposed to maltreatment tend to show more antisocial and aggressive behaviors. Simultaneously, recent evidence has suggested that this tendency would happen also in women but in those with high MAO-A activity genotype (Aslund et al, 2011;Byrd & Manuck, 2014;McGrath et al, 2012;Prom-Wormley et al, 2009;Sjöberg et al, 2007;Verhoeven et al, 2012;Wakschlag et al, 2010). MAOA has been related to other mental health problems in addition to antisocial behaviors.…”
Section: Introductionmentioning
confidence: 99%